Semantic Change Analysis on Film “the King’s Speech” - Hidayati Hidayati; Ilham Ilham (Linguistics and ELT Journal, 2018)
Semantic Change is the meaning of a word can indeed change through its use in a metaphor, and it is often mentioned as one of the significant factors in semantic change. Based on the types of semantic change, they are divided into four types namely generalization, specialization, pejoration and amelioration. This research aims to analyze semantic change by characters on the film The King’s Speech written by David Seidler to find the types of semantic change by using qualitative research, and the data were collected through the film script especially from the characters in the film. Based on the findings of the study, the researcher found two semantic change such as the semantic change of generalization reaches the highest number with 10 data (62.5%). It implies that the characters in the film gave the words which were containing the meaning of a word is broadening to include new concepts. The range of its meaning increases so that the word can be used in various contexts with a broader meaning than its neutral one. The semantic change of specialization with 6 data (37.5%). It implies that the characters in the film gave the words which were containing the meaning of the word is narrowed into the same class. The range of its meaning is decreased, and word can be used only in fewer contexts than before.